THE EFFECT OF MILITARY EXPENDITURES ON ECONOMIC GROWTHAND UNEMPLOYMENT: EVIDENCE FROM TURKEY - Ceyhan, Turgay; Kostekçı, Ahmet (My University, 2021)
Nowadays, military expenditures have an important share in public expenditures of countries. Although military expenditures have an important share in public expenditures, it is considered that military expenditures are unproductive in the economic growth and development process. The point in question, increases in military expenditures may cause less spending on economic and social fields. Less resource allocation to economic and social fields affects growth and employment. Thus, in this study, it is aimed to investigate the effect of military spending on economic growth and unemployment in Turkey. A data set which based on the period 1988-2019 was used to examine the relations between variables. According to the findings of Maki (2012) cointegration test, a cointegration relationship was found between military expenditure (ME), economic growth (EG) and unemployment (UNEMP). The FMOLS estimator was used for the estimation of long-term coefficients in the study. According to the results, it has been determined that military expenditures increase economic growth and unemployment in the long-term. This results showed that military expenditure led to growth that not based on employment in Turkey.
Keywords: İktisat